2022
DOI: 10.3389/fimmu.2021.788211
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on PD-1 Blockade and PD-1 Gene-Editing of CAR-T Cells for Glioma Therapy: From Deciphering to Personalized Medicine

Abstract: BackgroundProgrammed cell death protein 1 (PD-1) can attenuate chimeric antigen receptor-T (CAR-T) cell-mediated anti-tumoral immune responses. In this regard, co-administration of anti-PD-1 with CAR-T cells and PD-1 gene-editing of CAR-T cells have been suggested to disrupt this inhibitory axis. Herein, we aim to investigate the advantages and disadvantages of these two approaches and propose a novel strategy to ameliorate the prognosis of glioma patients.MethodsScopus, Embase, and Web of Science were systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…[27,38,39] Within the context of CAR T-cell treatment PD-1 suppression can be achieved through the co-administration of PD-1 targeting monoclonal antibodies or the PD-1 gene editing of CAR T-cells. [40] In systemic tumor models, the additional value of PD-1 blockade to increase CAR T-cell e cacy has been debated. In a murine preclinical model for systemic melanoma, concurrent PD-1 blockade notably increased the persistence and e cacy of CAR T-cell treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[27,38,39] Within the context of CAR T-cell treatment PD-1 suppression can be achieved through the co-administration of PD-1 targeting monoclonal antibodies or the PD-1 gene editing of CAR T-cells. [40] In systemic tumor models, the additional value of PD-1 blockade to increase CAR T-cell e cacy has been debated. In a murine preclinical model for systemic melanoma, concurrent PD-1 blockade notably increased the persistence and e cacy of CAR T-cell treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PD-1 knock-out had a positive effect on CAR-T cell survival, but such manipulation can cause significant adverse reactions, thus the individual risk of gains and losses should be kept in mind. 13 Transforming growth factor β (TGF-β) negatively affects the efficacy of CAR-T therapy, as one of its functions in tumor microenvironment (TME) is immunosuppression limiting the role of T cells. 14 Tang et al 14 attempted to block TGF-β at the tumor site by using nano-techniques to deliver TGF-β inhibitors LY2157299 (LY), and obtained LY/ICG@HES-PCL nanoparticle.…”
Section: The Importance Of Treatment Personalizationmentioning
confidence: 99%
“…Insufficient persistence of CAR T‐cells in vivo remains a significant clinical problem. It has been shown that PD‐1 knock‐out had a positive effect on CAR‐T cell survival, but such manipulation can cause significant adverse reactions, thus the individual risk of gains and losses should be kept in mind 13 . Transforming growth factor β (TGF‐β) negatively affects the efficacy of CAR‐T therapy, as one of its functions in tumor microenvironment (TME) is immunosuppression limiting the role of T cells 14 .…”
Section: The Importance Of Treatment Personalizationmentioning
confidence: 99%
“…It has been shown that the PD-1/PD-L1 axis contributes to CTL exhaustion and Treg augmentation, which protects tumor cells from CTL-mediated lysis ( 159 ). These findings call for more research into integrating anti-PD-L1 or genetically engineered T cells with PD-1 receptor blockade with CMV-specific ACT to maximize the clinical response of GB patients with predominant PD-L1 expression ( 160 ).…”
Section: Cmv-specific Adoptive T Cell Therapymentioning
confidence: 99%